THE CODE SWITCHING IN TEACHING AND LEARNING ENGLISH PROCESS FOR HEALTH INFORMATION MANAGEMENT STUDENTS AT DELI HUSADA DELI TUA HEALTH INSTITUTE - Herawati Br Bukit; Dila Fitria (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
Most of the students come from different areas, cultures and tribes. According to them, English is one of the difficult subject especially speaking comprehension. This situation makes them to use code switching. It also occur in English language learning. The main topic of this research focuses on psycholinguistic in the classroom teaching-learning process of foreign language, in this case English. Psycholinguistic roles in this research are limited to the code-switching processes which performed by the English lecturer that was happened intentionally or unintentionally in process of teaching and learning English for Health Information Management students at Deli Husada Deli Tua Health Institute. The lecturer made a code switching when she introduced new information or instruction. The switching also might occur when she translated what she has just said and when she introduced the interaction particles at the beginning of their utterances. Research results showed that Bahasa Indonesia or national language was one address of having code-switching and it had important role in English language learning. Although the English class should be formally full of the use of the learned language, switching process to Bahasa Indonesia took place naturally and the use of Bahasa Indonesia had psychological roles in order to improve learning motivation and full understanding for students.